METODE ECONOMIC QUANTITY INTERVAL (EOI) UNTUK OPTIMALISASI PERSEDIAAN BARANG CONSUMABLE ADEM SARI CHINGKU PADA PT SARI ENESIS INDAH CIAWI BOGOR - Anissa Ariesty; Titiek Tjahja Andari (Jurnal Visionida, 2016)
PT Sari Enesis indah is a company of engaged in the beverage industry. In this research will discuss about inventory control consumable goods in 2014 as well recommend the optimal inventory control method and optimalization of total cost for the company. In analyzing inventory control used method EOQ, EOI and min-max stock to compare and search the optimal result and according to the company. The result of analysis or calculation of inventory control will be reanalyzed used sensitivity analysis to determine whether the result of these calculation are sensitive or effect on the price changes of consumable goods caused by inflation West Java. The result of analysis that the optimal method and according with the company is EOI method, and the sensitivity analysis result that EOI method insensitive or no effect on the price changes of consumable goods.Keywords: Inventory Control, consumable Goods, EOQ, EOI, Min-Max, Sensitivity analysis